The Philosophy and Application of Panca Jiwa at Pondok Modern Darussalam Gontor-Ponorogo (A Field Study on Class 5 Dormitory Managers) - Rif’at Husnul Ma’afi; Khalifaturrahman Khalifaturrahman; Achmad Reza Hutama Al Faruqi; Nabila Huringiin (Educan : Jurnal Pendidikan Islam, 2021)
Pondok Modern Darussalam Gontor is an Educational Institution that has contributed a lot in printing cadres of leaders of the people. This can happen because Pondok has many philosophies of life, one of which is called Panca Jiwa. It is one of the values of Pondok that’s fixed, and solid, which must certainly be applied by the entire family, for their lives to be peaceful, safe, and in line with what has been outlined by it. Covering the spirit of sincerity, the soul of simplicity, the soul of self-reliance, the soul of Ukhuwah Islāmiyah, and the soul of freedom, Panca Jiwa becomes the basis or principle of the running of life in Pondok. Besides, 5 grade students as managers of hostels are senior students who are mandated by Pondok to educate their members, so in their daily lives they are obliged to practice the values contained in Panca Jiwa, but the implementation of Panca Jiwa faces a bit of a problem, that some managers of hostels have not implemented it properly. Therefore, this article aims to examine the philosophies of Panca Jiwa and it’s extent reflection in the activities of managers of hostels of 5 grade students at Pondok Modern Darussalam Gontor by using philosophical approaches as well as descriptive-analytical methods. Beside some previous studies discuss each philosophy of each Soul, while this research discusses philosophy and its application in the daily life of managers of hostels from 5 grade students of PMDG. Eventually, it was found that some managers of hostels had well applied every soul of Panca Jiwa as well.